2022
DOI: 10.1055/a-1839-5401
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of tumors of minor ampulla: a multicenter study

Abstract: Background and study aims Papillary and duodenal carcinoma are aggressive cancers with poor 5-year survival rates. Papillectomy is a well-established treatment for early-stage carcinoma of the major papilla. Tumors arising in the minor papilla are relatively rare and there is little research available on the endoscopic management of these tumors. Patients and methods The purpose of this study was to establish the safety and efficacy of endoscopic papillectomy in the management of minor papillary tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…9 Though endoscopic resection of the minor papilla neoplasia is seldom reported, case reports and small case series have suggested that EP is also an alternative treatment for minor papillary tumors. 10,18 The most common indication for EP is benign adenoma of the pancreatic duct or bile duct with no intraductal involvement. 19 Surgical resection is required for malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…9 Though endoscopic resection of the minor papilla neoplasia is seldom reported, case reports and small case series have suggested that EP is also an alternative treatment for minor papillary tumors. 10,18 The most common indication for EP is benign adenoma of the pancreatic duct or bile duct with no intraductal involvement. 19 Surgical resection is required for malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, studies have revealed that EP is a safe and minimally invasive alternative to pancreatoduodenectomy for the treatment of ampullary adenoma 9 . Though endoscopic resection of the minor papilla neoplasia is seldom reported, case reports and small case series have suggested that EP is also an alternative treatment for minor papillary tumors 10,18 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations